The Effect Of Zakat, Infaq And Alms (Zis) On Indonesia’s Economic Growth: Ardl Method - Ardiansyah Habibi Harahap, Rocky; Tri Ana Harahap, Choirunnisa; Evy Cahyani, Utari (Proceedings of International Conference on Islamic Economic Finance and Social Finance (ISSN: XXXX-XXXX) (ESSN: XXXX-XXXX), 2021)
Zakat, Infaq and Sadaqah (ZIS) is an instrument of Islamic philanthropy that has an important role in society and can encourage economic growth through income redistribution and reduction of social inequality in Indonesia. For a Muslim, it is obligatory to pay zakat, while spending money on infaq and alms is sunnah. ZIS funds are expected to be channeled to the poor who need (mustahik) to improve their welfare in order to achieve economic growth of the Indonesian people. The period in this study is ZIS and Economic Growth in Indonesia 2002-2019. This research uses the Autoregressive Distributed Lag (ARDL) method. This type of research is quantitative research with data analysis techniques using the Autoregressive Distributed Lag (ARDL) method and data processing using the Eviews 10 application. The results showed that Zakat, Infaq, and Alms (ZIS) in the long run had an effect on Economic Growth in Indonesia that expected to be a policy for the government in managing ZIS funds.